Euthanasia in utilitarian bioethics. A critique of J Rachel's and H Kuhse's books. - Reichlin, Massimo (Medicina e Morale, 1993)
The Author examines the critiques presented by Rachels and Kuhse, two major scholars in Anglo-Saxon utilitarianism, to the sanctity-of-life doctrine, with particular reference to the problem of euthanasia. Both authors show a radical misunderstanding of the nature of ethics, basically due to the strictly consequentialist nature of their theory. Utilitarianism thus shows its inadequacies in picking up the morally relevant characters of the complex situations presented by terminai illness. The Author then shows how the traditional principles of the double effect and of the proportionality of the means allow a better interpretation of the concrete experience of moral action.